2006
DOI: 10.1128/mcb.00893-06
|View full text |Cite
|
Sign up to set email alerts
|

The Polypyrimidine Tract Binding Protein (PTB) Represses Splicing of Exon 6B from the β-Tropomyosin Pre-mRNA by Directly Interfering with the Binding of the U2AF65 Subunit

Abstract: Splicing of exon 6B from the ␤-tropomyosin pre-mRNA is repressed in nonmuscle cells and myoblasts by a complex array of intronic elements surrounding the exon. In this study, we analyzed the proteins that mediate splicing repression of exon 6B through binding to the upstream element. We identified the polypyrimidine tract binding protein (PTB) as a component of complexes isolated from myoblasts that assemble onto the branch point region and the pyrimidine tract. In vitro splicing assays and PTB knockdown exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 55 publications
5
77
0
Order By: Relevance
“…65,2008 Review Article 521 to function through an interaction with PTB, and might facilitate the identification of novel PTB targets. For example, many studies identified PTB binding sites by boundary analyses, gel shift experiments and cross-linking [10,15,22,32]. In light of the complex structures [85], these findings can be more easily interpreted.…”
Section: How Can the Ptb Structures Explain Its Multiple Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…65,2008 Review Article 521 to function through an interaction with PTB, and might facilitate the identification of novel PTB targets. For example, many studies identified PTB binding sites by boundary analyses, gel shift experiments and cross-linking [10,15,22,32]. In light of the complex structures [85], these findings can be more easily interpreted.…”
Section: How Can the Ptb Structures Explain Its Multiple Functionsmentioning
confidence: 99%
“…The distribution of PTB binding sites within introns has led to several proposed models of PTB action. For example, PTB could interfere with spliceosome assembly by binding to the branch point pyrimidine tract and therefore directly sequestering the branch-point or competing with U2AF, an essential component of the constitutive splicing machinery [2,15,22,32]. In most cases, however, the exons silenced by PTB are flanked by PTB binding sites on both adjacent introns, and mutations of upstream PTB binding sequences have been shown to reduce binding of PTB to the downstream sites [7].…”
Section: The Many Functions Of Polypyrimidine Tract Binding Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…One example for positiondependent splicing is constituted by the hnRNP protein PTB (Xue et al, 2009;Llorian et al, 2010), an in animals, wellcharacterized regulator of AS that binds to pyrimidine-rich motifs within pre-mRNAs (Sawicka et al, 2008;Wachter et al, 2012). Evidence has been provided that PTB exploits various mechanisms for AS control, including competing with U2 auxiliary factor 65 in binding to the pre-mRNA (Saulière et al, 2006), looping of RNA regions (Spellman and Smith, 2006), and interference with splicing factor interactions required for exon or intron definition (Izquierdo et al, 2005;Sharma et al, 2005). In animals, a switch in expression from PTB to its neuronal homolog nPTB was shown to reprogram AS patterns and coincides with neuronal development (Boutz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The observation that in the absence of UTE, a 2-fold increase in exon 9A9Ј usage was still observed when PTB was down-regulated strongly suggests that in addition to precluding the assembly of an activator complex onto UTE, PTB directly inhibits the 3Ј splice site and ␣e poly(A) site selection by the basal splicing and cleavage/polyadenylation machineries. Since numerous high affinity PTB binding sites are present between the Ϫ274 distal branch site and exon 9A9Ј, it is likely that PTB inhibits the splicing of exon 9A9Ј by directly preventing the binding of U2AF65, as described for the mutually exclusive exon 6B of the ␤-tropomyosin pre-mRNA (21). It is also conceivable that PTB blocks the transition from an exon 9A9Ј defined complex to a functional spliceosome, as demonstrated for the regulation of the alternative exon N1 of the c-src pre-mRNA (26).…”
Section: Discussionmentioning
confidence: 99%